ISOLASI DAN KARAKTERISASI BAKTERI MANOLITIKASAL BONGGOL POHON SAGU - WAHYUNI, SRI; -, LIANTO; KHAERUNI, ANDI (Jurnal Agroteknos, 2014)
Sago Processing in Southeast Sulawesi often generate waste in the form of pulp and tuberswhich contains lignin, cellulose, starch, minerals, and vitamins that can be used as a source of carbon and energy for growth of microorganisms, so it is likely to get microbes, including mannolitic bacteria that are useful for human life. The aim of this study was to isolate and characterize the biochemical properties of mannolitic bacteria originated fromwaste of sago hump in Konawe, Southeast Sulawesi Province. Isolation was done using serial dilution method and then spread over the surface of Nutrient agar medium and Mannan enrichment. Bacterial isolates showing high mannose activity were characterized mannose physiologically and biochemically. From this research, 6 mannolitic isolates originated from hump of sago waste samples from South Konawe were obtained. BLS.11-01 and BLS.11-02 mannolitic bacterial isolates had a strong mannolitic activity, with mannolitic index value of 2.3 and 2.0, respectively. Presumably, the two isolates were gram-positive bacteria, belonging to the same genus.